Creating wealth through social entrepreneurship : a case study from Malaysia - Mhd. Sarif, Suhaimi; Ismail, Yusof; Sarwar, Abdullah Al-Mamun (TextRoad Publication, 2013)
Social entrepreneurship has become a common interest among the academicians and practitioners due to its enormous opportunities to challenge, question and rethink concepts and assumptions from different fields of management and business research. This study was carried out to understand the social entrepreneurship phenomenon in the context of developing nations such as Malaysia. The main purpose of this study was to explore a particular social phenomenon on how wealth can be created through social entrepreneurship. A qualitative case study approach was adopted since this facilitates in assessing and evaluating the particular phenomenon more intensely. Data had been collected through interviews which were conducted over a three-week period around Klang Valley, Malaysia. Convenient sampling method was adopted to identify the respondents for this study. This study has highlighted few of the important components of social entrepreneurship in Malaysia such as overall concept regarding social entrepreneurship, motivation for involvement and value creation. This study believes that lack of political commitments and absence of creation healthy environment required for social entrepreneurial growth are the limiting factors in the process of the adequate supply of reasonable number of social entrepreneurs. Firm commitments of the power cliques, aggressive efforts in creating entrepreneurial environment besides provision for all essential common support services and assistance may speed up the supply of social entrepreneurs in Malaysia.